Prevalence and Risk Factors of Scabies: Observational Study in Nurul Ilmi Darunnajah 14 Islamic Boarding School Students in Serang, Banten, Indonesia - Hans Sugiarto; Song, Chrismerry (HM Publisher, 2024)
Scabies is a contagious skin condition triggered by Sarcoptes scabiei varietas hominis. It is prevalent globally, particularly in tropical regions with low economic resources. The condition is commonly observed in densely populated environments characterized by close physical contact, such as Islamic boarding schools. This cross-sectional research was conducted in December 2023 at the Nurul Ilmi Darunnajah 14 Islamic Boarding School. This research involved 120 students who met the inclusion criteria. The questionnaire contains informed consent, personal identity, 15 questions to assess the level of personal hygiene, 15 questions to assess the respondent's level of knowledge, 8 statements, and 2 inspection points related to scabies diagnostic criteria. The data obtained will then be analyzed and researched according to the diagnostic criteria of the 2020 International Alliance for the Control of scabies consensus criteria for the diagnosis of scabies. The prevalence of scabies in this Islamic boarding school is 22.5% (27/120), with the risk factor for scabies being the level of personal hygiene, which includes individual cleanliness, environmental cleanliness, direct contact, ventilation, and humidity of the bedroom.